(untitled) (Medico Legal Update, 2021)
Objective: Thyroid disorders are the most common endocrine disorders worldwide (4-7% of population). Excision of all thyroid lesions is impractical. For rapid diagnosis, Fine needle aspiration cytology (FNAC) is simple, safe, rapid diagnostic procedure. However, indeterminate cases were reported occasionally where the patient cannot be confidently assigned to a manageable category. Aim: We conducted a systematic review and meta-analysis to evaluate the diagnostic accuracy of FNAC in thyroid lesions and the correlation between cytological and histopathological diagnosis. Method: A literature search of published studies was conducted using Medline/PubMed, reasearchgate, Scielo (scientific electronic library online), and Google Scholar as international databases, and IVSL (Iraqi Virtual Science Library) and IASJ (Iraqi Academic Scientific Journals) as national databases. Results: A total of 24 studies are analyzed. The median sample size of the studies included was 100 (range, (20?23)5). The sensitivity and specificity ranged from 0.38 to 0.98 (pooled sensitivity: 0.81; 95% confidence interval (CI), 0.78?0.83) and from 0.47 to 1.00 (pooled specificity: 0.93; 95% CI, 0.92?0.94), respectively. By SROC curve, the Q-value was 0.883 and the area under the curve (AUC) was 0.945, indicating a high level of overall accuracy. Conclusion: The recognized accuracy of FNAC in detecting thyroid cancers is applicable only to papillary carcinoma and not to other malignancies. Moreover, FNAC should be considered as a screening rather than diagnostic tool for follicular lesions. Thus, FNAC helps to orientate patient management rather than to provide final definitive diagnosis.